X-ray induced reduction of Sm3+ into Sm2+ in Li2CaSiO4 and its potential for radiation measurement applications. (March 2023) - Okada, Go; Ikenaga, Noriaki; Koguchi, Yasuhiro; Yanagida, Takayuki; Kasap, Safa; Nanto, Hidehito
Highlights: Reduction of valence state of Sm3+ to Sm2+ doped in Li2CaSiO4 is induced by X-ray irradiation. Photoluminescence intensity of Sm2+ can be used as a probe of accumulated radiation dose. Oxidation of Sm2+ to Sm3+ is induced by heat-treatment. X-ray induced reduction of Sm3+ in Li2CaSiO4 is reproducible multiple times. Abstract: In Sm 3+ -doped Li2 CaSiO4, the Sm 3+ ion is reduced to the Sm 2+ state by X-ray irradiation. The valence change was confirmed by the difference in their photoluminescence spectra, measured before and after irradiation. Only luminescence peaks due to the 4f-4f transitions of Sm 3+ are observed before the irradiation while an additional luminescence band is observed at 900 nm due to the 5d-4f transition of Sm 2+ . The reaction is that a fraction of X-ray generated electrons is captured by Sm 3+ ions, which convert to the Sm 2+ state. The generated Sm 2+ state is fairly stable while it is effectively reversed back to the Sm 3+ state by a heat treatment at an elevated temperature. A numerical approximation revealed the activation energy to be 0.40 and 0.52 eV. Even after the heat-treatment, the reduction of Sm 3+ to Sm 2 + is reproducible multiple times, which shows good potential for using radiation measurement applications. Graphical abstract: Image, graphical abstract